Assessment of micronutrient extractants from soils of Paraná, Brazil - Mansano Sarto, Marcos Vinicius; Steiner, Fabio [UNESP]; Lana, Maria do Carmo (Sociedade Brasileira de Ciência do Solo, 2011)
In Brazil, plant-available micronutrients in the soil can be determined by several chemical extractants, the most common of which are dilute acid and chelating solutions. The purpose of this study was to assess the extractants 0.1 mol L-1 HCl, Mehlich-1, Mehlich-3 and DTPA for analysis of the micronutrients Cu, Zn, Fe, and Mn in soils from the state of Parana. In samples from 12 soils (0-20 cm layer), wheat was planted (Triticum aestivum), grown for 42 days after emergence, and then bean (Phaseolus vulgaris) for 38 days. At the end of each planting period, the soil was sampled again. All extractants tested to assess the availability of Cu, Zn, Fe, and Mn correlated with each other. The efficiency of the extractants HCl, Mehlich-3 and DTPA in assessing plant-available Cu was similar, unlike Mehlich-1, which proved less efficient. The extractants HCl, Mehlich-1 and Mehlich-3 were less efficient in estimating plant-available Zn and Fe, and the most indicated extractant is DTPA. The efficiency of the extractants HCl, Mehlich-1, Mehlich-3 and DTPA in assessing plant-available Mn in soils from Parana was similar.

No Brasil, diversos extratores químicos são utilizados na determinação de micronutriente disponível para as plantas, destacando-se soluções ácidas diluídas e quelatantes. Neste trabalho, objetivou-se avaliar os extratores HCl 0,1 mol L-1, Mehlich-1, Mehlich-3 e DTPA, para análise dos micronutrientes Cu, Zn, Fe e Mn em solos do Estado do Paraná. Amostras de 12 solos coletadas da camada de 0-20 cm de profundidade foram cultivadas com plantas de trigo (Triticum aestivum) por 42 dias e, em sequência, com plantas de feijão (Phaseolus vulgaris) por 38 dias após a emergência. No final de cada cultivo foram coletadas amostras do solo. Todos os extratores testados para avaliar a disponibilidade de Cu, Zn, Fe e Mn correlacionaram entre si. Os extratores HCl, Mehlich-3 e DTPA apresentaram eficiência semelhante na avaliação da disponibilidade de Cu às plantas, já o Mehlich-1 foi menos eficiente em estimar a disponibilidade desse elemento. Os extratores HCl, Mehlich-1 e Mehlich-3 foram menos eficientes para estimar a disponibilidade de Zn e Fe para as plantas, sendo o DTPA o extrator mais indicado para tal. Os extratores HCl, Mehlich-1, Mehlich-3 e DTPA mostraram eficiência semelhante na avaliação da disponibilidade de Mn para as plantas em solos do Paraná.
Avaliação de extratores de micronutrientes em solos do Paraná
Keywords: soil analysis; correlation; copper; zinc; iron; manganese